Design Formulation of Nanospanlastic Novel Carriers as a Promising Approach to Enhanced Bioavailability in Intranasal Drug Delivery for Sinusitis: Statistical Optimization and In vitro and In vivo Characterization - Chettupalli, Ananda K.; Ajmera, Srivani; Kuchukuntla, Mounika; Palanivel, Venkatesan; Katta, Sunand (Current Nanomedicine, 2024)
Background: Most new biologically active chemicals require better water solubility and slower dissolution rates. Cefdinir (CFD) has a very low bioavailability in its crystalline form and is poorly soluble in water. Objective: By preparing cefdinir's spanlastic nanovesicles (SNVs) using the ethanol injection method, the current study has attempted to enhance the drug's solubility and bioavailability using a statistical design approach. Methods: Independent variables, including the nonionic surfactant concentration, edge activator (EA), sonication time, SNVs entrapment efficiency, particle size, zeta potential, PDI, and in vitro release, have been evaluated. The best CFD-SNVs were positioned within in situ gel with mucoadhesive properties made of hydroxypropyl methylcellulose and deacetylated gellan gum. By contrasting intranasal injection of the produced gel with an IV solution, animal models have been used to investigate CFD's systemic and cerebral dynamics. Results: Statistical analysis has suggested an ideal SNVs formulation with nonionic surfactant (65 mg), EA (15 mg), and sonication (3 min). The sol-gel temperature for forming the mucoadhesive in situ gel containing SNVs has been found to be 34.03°C, and 18.36 minutes has been the extended mucociliary transit time. Following intranasal injection, compared to SNV dispersion, the gelling system has exhibited higher brain bioavailability (2251.9 ± 75 vs. 5281.6 ± 51%, respectively). The gel has also demonstrated effective drug targeting of the brain with higher direct transport percentage indices. Conclusion: Mucoadhesive in situ gel with CFD-loaded SNVs can be administered via the intranasal route. To enhance bioavailability in the brain and drug targeting from the nose to the brain, nasal in situ gel loaded with CFD-SNVs could be a new carrier to be employed in sinusitis.
Keywords: spanlastic nanovesicles